COVID‐19 and Alzheimer's disease: Meninges‐mediated neuropathology. (December 2021) - Raval, Urdhva; Trageser, Kyle J; Naughton, Sean X; Griggs, Elizabeth; Iqbal, Umar Haris; Wu, Henry; Rahim, Md Al; Harary, Joyce M; Gursahai, Susan; Pasinetti, Giulio Maria
Abstract: Background: SARS‐CoV‐2 the causative agent of COVID‐19 displays a broad range of pathophysiology. Cytokine storms associated with COVID‐19 damage the blood‐brain barrier (BBB) and allow pro‐inflammatory factors to invade the brain, further promoting neurodegeneration. While SARS‐CoV‐2 viral RNA and proteins have been detected in brain tissues, the mechanisms of neuroinvasion remain unknown. COVID‐19 has had a disproportionate impact on those suffering from neurodegenerative disorders such as Alzheimer's disease (AD). Understanding the mechanisms of SARS‐CoV‐2 neuroinvasion is crucial to study the long‐term neurocognitive effects of COVID‐19 on AD pathology. Viruses can infiltrate the brain through the meninges via infected immune cells. The meninges regulate the immune surveillance of the brain and play a key role in the efflux of pathogens from the brain. Meningeal dysfunction has been demonstrated to exacerbate amyloid‐beta pathogenesis. In this study, we explore the neuroinvasion pathway of SARS‐CoV‐2 through the meninges and its effect on AD pathology. Method: 5x FAD x hACE2 mice were inoculated intranasally with a sublethal dose of SARS‐CoV‐2. The mice were maintained for 2 weeks. Mouse brains and meninges were harvested. The tissue was stained and immunofluorescence imaging was conducted to study viral proliferation and immune responses. Histo‐cytometry was conducted for quantitative imaging analysis. Gene expression studies were done using Nanostring assays. All experiments involving the SARS‐Cov‐2 virus were carried out in a BSL3 facility. Result: This ongoing study demonstrates the proliferation of the SARS‐CoV‐2 virus in the brain via meningeal lymphatics. SARS‐CoV‐2 infection resulted in increased neuroinflammation. Additionally, inflammatory responses induced meningeal dysfunction resulting in increased amyloid‐beta pathology and cerebrospinal fluid drainage. Conclusion: Given the increasing evidence for a viral hypothesis of Alzheimer's Disease it is extremely important to study the neurodegenerative effects of COVID‐19 which has affected millions worldwide. We demonstrate that SARS‐CoV‐2 infiltrates the brain via the meninges promoting neuroinflammation. Furthermore, amyloid‐beta pathologies are exacerbated by COVID‐19 in animal models providing preclinical evidence of the long‐term neurodegenerative effects of COVID‐19.